Highly Customizable Transparent Silver Nanowire Patterning via Inkjet‐Printed Conductive Polymer Templates Formed on Various Surfaces. Issue 6 (17th March 2020) - Park, Jongjang; Kim, Geonhee; Lee, Byeongmoon; Lee, Seunghwan; Won, Phillip; Yoon, Hyungsoo; Cho, Hyeon; Ko, Seung Hwan; Hong, Yongtaek
Abstract: Silver nanowires (AgNWs) have been considered as replacements of indium tin oxide (ITO) due to superior optoelectronic properties and mechanical stability for flexible electronics. However, high cost and process complexity of patterning process disturb their applicability to commercial products. Herein, a facile patterning method of AgNWs by using inkjet‐printed conductive polymer templates is developed, which can be applied on various surfaces including super hydrophobic light‐emitting organic layer. Combination of inkjet and transfer printing processes rendered high degree of freedom both in customizing patterns and in tuning transparency and conductivity simultaneously. AgNWs are selectively transferred from a donor elastomer onto formulated adhesive conductive polymer patterns. By changing thickness of the AgNW networks flood‐coated on the elastomer, their transparency and conductivity can be tuned during the transfer process. AgNW transparent electrodes on plastic substrates have much higher figure of merit than that of ITO on plastic substrate. The selective transfer process simultaneously solves inherent issues of the AgNW electrodes such as poor adhesion to various surfaces, surface roughness, and fine pattern formation. Finally, with superior optoelectronic property and mechanical flexibility of the electrodes, various flexible electronic applications are demonstrated. Abstract : Silver nanowire (AgNW)‐transferred poly (3, 4‐ethylenedioxythiophene):poly (styrenesulfonate) is fabricated by combination of inkjet‐printing of transfer template and selective transfer of AgNWs onto the template. This patterning method ensures high degree of freedom without need of high equipment cost and process complexity. With maintaining advantages and overcoming issues of the AgNWs, the method can be applied to various flexible electronics.